Oral postcoital contraception and pharmacological abortion: product characteristics and basic trade issues in Poland under pharmaceutical law, taking into account the international context - Gęsiak, Katarzyna (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The chapter analyses the trade in emergency contraceptives and abortifacient pills, their characteristics, and their status under Polish law, considered in an international context. Substances used in emergency contraceptive pills have an early abortifacient effect; although Polish regulations market them as contraceptive medicinal products, their nature justifies reclassifying them as abortifacients, whose sale is prohibited by law, as is the online sale of abortion products, requiring enforcement, since in internet crimes the perpetrator's place of operation includes the location of the computer system used. Under EU law, states may prohibit or limit trade in contraceptives and abortifacients, further justified where oral emergency contraception has proven anti-implantation properties. Polish legislation should be supplemented with a definition of pregnancy differing from the World Health Organization's, reflecting the constitutional principle of protecting life from conception.